Improving products and services of AGRHYMET climate information portal with Next Generation Seasonal Forecasts - Halidou, Tinni Seydou; Mainairassa, Azziz; Mohamed, Hamatan; Agali, Alhassane; Ali, Abdou; Segnon, Alcade C; Zougmoré, Robert B. (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
The PyCPT is operational at the RCC-WAS. Seasonal forecasts (NextGen) are generated monthly. Seasonal forecast products (NextGen) are posted on the RCC-WAS portal and updated regularly